All-carbon composites and hybrids - Kharissova, Oxana Vasilievna; Kharisov, Boris I. (Royal Society of Chemistry, 2021)
Providing a broad overview of all-carbon composites and their applications this book is a useful reference for material scientists and researchers working in nanotechnology.
Keywords: Carbon composites.; Nanostructured materials.; elektronické knihy; electronic books